(untitled) (Eduscotech, 2022)
Special Education (PLB) teacher training for children with autism in East Java aims to enhance teacher competence and improve the quality of instruction for students with Autism Spectrum Disorder (ASD). As the number of children diagnosed with autism continues to increase, the demand for well-trained and skilled special education teachers has become increasingly urgent. This study focuses on identifying the fundamental needs of PLB teachers in working with children with autism, as well as effective training approaches to support the development of their professional skills. The training program employed a combination of theory-based and practice-based approaches, enabling participants to gain a comprehensive understanding of the characteristics of children with autism, appropriate communication strategies, and individualized teaching techniques. Through structured training sessions, teachers were equipped to design adaptive learning activities and implement instructional strategies that address the diverse needs of students with autism. The results of this training are expected to strengthen teachers’ abilities to create inclusive learning environments, support students’ social-emotional development, and improve overall educational quality for children with special needs. This study also offers recommendations for sustainable teacher training programs and highlights the importance of aligning regional education policies with inclusive education initiatives to further support children with autism in East Java.